Visitor management mobile application for public school / Muhammad Rais Helmi Md Aris - Md Aris, Muhammad Rais Helmi (2022)
This report is mainly discussed the design and develop the Visitor Management Mobile Application as an application that manages all of the visitors that visited the school. School visitor management is a mobile application that helps to manage the visitors that wish to enter the school. The visitors can be a parent, relatives, or friends. This system will help to manage the visitors by needing them to fill in the visiting form in the application at least three days before visiting. It gives the school admin access to manage their visitors. It is possible because the visitors need to sign in and request the visit so that only the accepted an authorized visitor can enter the school. Currently, many public schools in Malaysia only uses basic security measure by filling in forms manually. This shows that the current filling system for visitor management is very poor. In cases where student abduction or sudden disappearance without trace may happen, the school cannot refer to the visitor history as a reference. So, with help of this mobile application, hopefully it will improve the school security and the management of visitors will become smoother than before. For the testing phase, this application used functionality testing and user acceptance testing. The result for the functionality testing of this application is pass while the result for user acceptance testing also pass by the stakeholder. However, there are still some improvements that can be done in this application for future work.